EFEKTIVITAS PENAGIHAN PAJAK DENGAN SURAT TEGURAN DAN SURAT PAKSA TERHADAP PENERIMAAN PAJAK - Filmon Nalle, Paul (E-Jurnal Akuntansi, 2017)
The phenomenon of tax compliance is quite the spotlight because of tax compliance in Indonesia is very low. The rights and tax obligations undertaken by all the taxpayer, the government, especially the Tax Office is obliged to provide guidance in the form of information dissemination and extension of tax, administrative services, as well as carry out supervision on tax compliance by conducting inspections and tax collection. The purpose of this study was to know the level of effectiveness of tax collection with a letter of reprimand and forced letter in order to optimize tax revenue on STO Singaraja. This study took place in the Tax Office (KPP) Pratama Singaraja. The data analysis technique used to test the hypothesis is descriptive analysis techniques to determine the level of effectiveness of tax collection with a letter of reprimand and forced letter. Based on the results of data analysis known that the average percentage of the effectiveness of tax collection with the condition Warning Letter and Letter Forced found to be ineffective.
Keywords: letter of reprimand, forced letter